Effect of Tandem Flocculation Agent System on Lime Mud NPE (Non Process Element) - Ahmad Wahyu Shaputra; Rachmawati Apriani (Eksergi, 2022)
Non Process Element (NPE) is an impurity substance that is not expected to be present in the caustic system because it can cause disruption to the process and affect the product quality. One way to minimize NPE input is through the process of clarifying raw green liquor into clean green liquor using the coagulation-flocculation method with PDADMAC and A-PAM chemicals. The aim of this study is to determine the effect of tandem flocculation agent system on lime mud NPE taking into account the quality standards of several Non Process Element (NPE) compounds in lime mud, as follows : P2O5 <1%, SiO2 < 0.5%, MgO < 0.75%, Fe2O3 < 0.3%, Mn2O3, and Al2O3 < 0.5%. The clean green liquor production uses variations in PDADMAC doses (0, 3, and 5 ppm), while the A-PAM dose is fixed at 7 ppm for each variation. The results show that the optimal dose ratio of PDADMAC: A-PAM from a technical point of view is the second variation ( PDADMAC 3 ppm: A-PAM 7 ppm), where the P₂O₅ value : 0.7159%, SiO2 : 1.4856%, MgO : 0.2234%, Fe2O3 : 0.2568%, Mn2O3 : 0.0055% , and Al2O3 : 0.5988%. But, the SiO2 and Al2O3 compounds at this dose ratio still exceed the lime mud quality standard. However, the dose ratio of PDADMAC 3 ppm : A-PAM 7 ppm showed more significant result than the other ratios.